2014
DOI: 10.1002/ijc.29180
|View full text |Cite
|
Sign up to set email alerts
|

Viral infections and colorectal cancer: A systematic review of epidemiological studies

Abstract: Numerous studies have found the presence of viral DNA in colorectal tumor tissues. However, whether viral infections contribute to the risk of colorectal cancer (CRC) is still under debate. We aimed to provide an overview of published epidemiological studies on the association between viral infections and CRC. A systematic literature search was performed in PubMed to find relevant studies published until 8 May 2014. Information collected included study population, sample type, laboratory method and prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 85 publications
0
69
2
1
Order By: Relevance
“…High-risk HPV DNA has been found in some unconventional HPV cancers, such as breast, prostate, colorectal, and lung cancers, and a causative role has been implied (210)(211)(212)(213). Although known to be associated with human cancers, the potential role of high-risk HPV in the carcinogenic steps of these cancers is controversial.…”
Section: Future Challengesmentioning
confidence: 99%
“…High-risk HPV DNA has been found in some unconventional HPV cancers, such as breast, prostate, colorectal, and lung cancers, and a causative role has been implied (210)(211)(212)(213). Although known to be associated with human cancers, the potential role of high-risk HPV in the carcinogenic steps of these cancers is controversial.…”
Section: Future Challengesmentioning
confidence: 99%
“…A recent review reported a higher prevalence of HPV in CRC tumors than noncancerous tissue 19. An earlier review of HPV and CRC also concluded that HPV may be associated with a subset of CRC 20.…”
Section: Introductionmentioning
confidence: 99%
“…As we cited above, lifetime risk of CRCs is estimated to be 5-6% in the general population of Western countries [45,46]. Although hereditary forms of CRC have been well established; however, most cases are sporadic [47].…”
Section: Introductionmentioning
confidence: 97%
“…In the past decades, Helicobacter pylori and Epstein Barr virus infections have been identified as potential causal factors of gastric cancer [50,51] and personal communication. A number of studies aimed to assess the possible role of viral infections, such as infection with high-risk HPVs, human polyomaviruses, and human herpesviruses in colorectal carcinogenesis [7,45,52,53]. Thus, in the next paragraph the presence and role of high-risk HPVs in human CRCs will be reviewed.…”
Section: Introductionmentioning
confidence: 99%